Small sample test technique 4th SSTT : selected, peer reviewed papers from the 4th International Conference SSTT "Detremination of Mechanical Properties of Materials by Small Punch and Other Miniature Testing Techniques", October 12-14, 2016, Shanghai, China - Guan, Kaishu; Matocha, Karel; Xu, Tong (Key engineering materials, 2017)
This collection is comprised of the papers presented at the 4th International Conference SSTT ,,Determination of Mechanical Properties of Materials by Small Punch and Other Miniature Testing Techniques" (October 12-14, 2016, Shanghai, China). It contains the research findings and the results of the application of the innovative testing techniques for evaluation of actual mechanical properties of the in-service structural components of industrial objects.